The integration of psychological services into primary health care (PHC) in South Africa : tensions in theory, policy and practice - Ameermia, Miriam Ginette (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Psychology))--University of Stellenbosch, 2009.